Controllable Synthesis of Leaf‐Like CuO Nanosheets for Selective CO2 Electroreduction to Ethylene. Issue 9 (6th April 2020) - Tan, Zhonghao; Peng, Tingyue; Tan, Xiaojie; Wang, Wenhang; Wang, Xiaoshan; Yang, Zhongxue; Ning, Hui; Zhao, Qingshan; Wu, Mingbo
Abstract: The carbon dioxide reduction reaction (CO2 RR) driven by renewable electricity is a promising way to tackle the CO2 emission woes and recycle use of CO2 . The synthesis of electrocatalysts with high activity and selectivity for CO2 RR to ethylene remains a great challenge. Herein, leaf‐like CuO nanosheets are fabricated in situ on nitrogen‐doped graphene (NG) by using a novel reduction‐oxidation‐reconstruction process. When used as a catalyst for the CO2 RR in 0.1 M KHCO3, a high faradaic efficiency of approximately 30 % for ethylene with an ultra‐high ethylene/methane ratio of 190 was achieved at −1.3 V vs. the reversible hydrogen electrode. The SEM and TEM images confirm the leaf‐like CuO nanosheets display high‐curvature structures, while multiple distinguished grain boundaries constructed by CuO(110) and CuO(111) planes are verified by HRTEM. For the first time, we present a facile method to combine the high‐curvature structure and the grain boundary to enhance the selectivity of the CO2 RR to ethylene over a CuO catalyst. Abstract : Take a leaf out of their book : Leaf‐like CuO nanosheets are synthesized, which show a high selectivity towards ethylene when used as catalysts for the electroreduction of carbon dioxide in aqueous solution. The benefits can be attributed to the high‐curvature structures and rich grain boundaries.